Two‐Dimensional Seeded Self‐Assembly of a Complex Hierarchical Perylene‐Based Heterostructure. Issue 38 (17th August 2017) - Liu, Yin; Peng, Cheng; Xiong, Wei; Zhang, Yifan; Gong, Yanjun; Che, Yanke; Zhao, Jincai
Abstract: A complex two‐dimensional (2D) hierarchical heterostructure was fabricated by a sequential two‐dimensional seeded self‐assembly, which consisted of laterally grown nanotubes from one perylene monomer and terminally elongated nanocoils from a similar perylene monomer on microribbon seeds from a third perylene. Because the nanotube and nanocoil monomers can form kinetically trapped off‐pathway aggregates to prevent self‐nucleation and have similar molecular organizations to different facets of the seeds, the nanotube and nanocoil monomers preferentially nucleate and grow on the seed sides and terminal ends, respectively, to form a complex 2D hierarchical heterostructure. The strategy used in this work can be extended to fabricate other complex nanoarchitectures from small molecules. Abstract : Location, location : A complex 2D hierarchical heterostructure was fabricated by a sequential seeded self‐assembly. This consisted of laterally grown nanotubes from a perylene derivative (blue) and terminally elongated nanocoils from a similar perylene (yellow) on a microribbon seed from a third perylene (red).